Validation of the X-ray microtomography in the assessment of duodenal morphometry and surface area in celiac disease - Virta, Johannes; Hannula, Markus; Lindfors, Katri; Tamminen, Ilmari; Taavela, Juha; Huhtala, Heini; Kaukinen, Katri; Saavalainen, Päivi; Hyttinen, Jari; Kurppa, Kalle (Frontiers in Immunology, 2022)
Background: Duodenal histology remains the diagnostic reference standard in celiac disease. However, traditional methods have suboptimal sensitivity and reproducibility for early mucosal changes and research purposes. We validated a recently introduced micro-CT imaging method for accurate digital evaluation of duodenal histomorphometry and mucosal surface areas. Methods: Endoscopic biopsies from 58 individuals were utilized for the micro-CT imaging, selecting histological changes ranging from normal to severely damaged mucosa. The imaging protocol was optimized for practicability and resolution. Bland-Altman method was applied to test intra- and interobserver variations in the blinded measurements. Results: The 3D micro-CT reconstructions enabled easy and precise digital cutting with optimal orientation and computer-assisted measurement of the surface area. Intraobserver analysis of morphological measurements showed a mean difference of 0.011 with limits of agreement (LA) from -0.397 to 0.375 and a standard deviation (SD) of 0.197. The corresponding figures for interobserver analysis were 0.080, from -0.719 to 0.537 and 0.320 respectively. Intraclass correlation coefficients (ICC) for the intraobserver and interobserver variations were 0.981 and 0.954 respectively. Intraobserver surface area analysis yielded a mean difference of 0.010, LA from -0.764 to 0.785 and an SD of 0.395, and an interobserver analysis mean difference of 0.028, LA from -0.642 to 0.698 and SD of 0.342. The respective ICCs for the intra- and interobserver variations were 0.963 and 0.972.. Conclusions: Micro-CT showed excellent accuracy and reproducibility in the evaluation of mucosal morphometry and surface areas. The improved sensitivity for histological changes is a powerful tool for the diagnosis of celiac disease and for clinical and pharmacological studies.